Importance of skills inventory and training in succession planning- how does it help in employee performance: The case of Heidelberg Cement Bangladesh Limited (HCBL), Chittagong Plant - Munira, Sirajum (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2022.